Reading Level Vis-À-Vis Academic Performance in English of Grade 6 Learners in Subic District - Arca, Kimberly B. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
This study was conducted to determine the Reading Level and Academic Performance of Grade 6 Learners in Subic District. The unit of analysis of the study was the 30 grade six Teachers of the said school who serve as respondents. This study focuses on the Reading Comprehension Level and Academic Performance of Grade 6 students in Subic District. The descriptive correlational research method was used in this study. To obtain the needed data the researchers administered a survey questionnaire to identify the challenges and strategies of Teachers in Teaching Reading which consisted of 30 items and collect the Academic Performance in 1st – 4th Quarter grades and Final average in English Subject. Aside from that the researcher collects the Philippine Informal Reading Inventory or Phil-IRI result of Grade 6 Students in School Year 2021-2022.The data were tabulated, analyzed and interpreted. The statistical tools employed in this study were the percentage, weighted mean and pearson (r). Based on the Findings, the researcher concluded the following: A typical teacher in the Grade 6 level in Subic district schools is a female mid-adult, married, has been in service to the Department of Education for at least half a decade with a general elementary education degree. The level of competencies that pupils have in letter recognition, fluency, vocabulary and comprehension; The teachers-respondents agreed that in the use of teaching reading strategies they have procedures and challenges encountered that they have remedies or strategies to address the challenges. There is a correlation between the learner’s learning competencies and teachers’ challenges and there is a significant relationship between reading level and academic performance in English of grade 6 Learners in selected schools of Subic District, Division of Zambales.